2011
DOI: 10.1038/nature10643
|View full text |Cite
|
Sign up to set email alerts
|

Natural polymorphisms in C. elegans HECW-1 E3 ligase affect pathogen avoidance behaviour

Abstract: Heritable variation in behavioural traits generally has a complex genetic basis1, and thus naturally occurring polymorphisms that influence behaviour have been defined in only rare instances2,3. The isolation of wild strains of Caenorhabditis elegans has facilitated the study of natural genetic variation in this species4 and provided insights into its diverse microbial ecology5. C. elegans responds to bacterial infection with conserved innate immune responses6-8 and, while lacking the immunological memory of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 30 publications
(42 reference statements)
5
101
0
1
Order By: Relevance
“…Then, after hours of exposure and presumed intestinal infection, C. elegans exhibits an altered preference for E. coli, suggestive of an aversive learning response [9] ( Figure 1A). In the absence of a choice between bacteria, when propagated monoaxenically on pathogens P. aeruginosa or Serratia marcescens, after an initial attractive phase, C. elegans exhibits a gradual evacuation of the bacterial lawn with kinetics comparable to the observed aversive learning response in the choice assay [10][11][12][13] ( Figure 1B). This lawn-leaving behavior likely reflects not only olfactory aversive learning but also the integration of multiple sensory cues from the bacterial lawn.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Then, after hours of exposure and presumed intestinal infection, C. elegans exhibits an altered preference for E. coli, suggestive of an aversive learning response [9] ( Figure 1A). In the absence of a choice between bacteria, when propagated monoaxenically on pathogens P. aeruginosa or Serratia marcescens, after an initial attractive phase, C. elegans exhibits a gradual evacuation of the bacterial lawn with kinetics comparable to the observed aversive learning response in the choice assay [10][11][12][13] ( Figure 1B). This lawn-leaving behavior likely reflects not only olfactory aversive learning but also the integration of multiple sensory cues from the bacterial lawn.…”
Section: Introductionmentioning
confidence: 89%
“…elegans can also use their mechanosensory neurons to respond to the texture of bacteria, slowing down once they have entered a bacterial lawn [6]. A naturally occurring polymorphism in the C. elegans E3 ubiquitin ligase HECW-1 affects lawn-leaving behavior by altering the mechanosensation of bacteria [13]. Reduction of function mutations in hecw-1 result in enhanced avoidance of P. aeruginosa.…”
Section: Microbial Cues and Chemosensationmentioning
confidence: 99%
See 2 more Smart Citations
“…Chang et al (2011) has demonstrated that pathogen avoidance by C. elegans can be affected by the lateral outer labial mechanosensory head neurons. tax mutants feeding on NZI7 grew well and showed no evidence of deleterious effects or pharyngeal dysfunction, allowing us to conclude that NZI7 is not intrinsically pathogenic to C. elegans and that the failure of wild-type nematodes to feed on it was due only to aversion and did not involve additional physical effects such as the pharyngeal blockage observed for C. elegans feeding on Y. pestis (Darby et al, 2002).…”
Section: Screen For Loss Of Nematode Repellencementioning
confidence: 99%